2013
DOI: 10.1073/pnas.1221180110
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalogram signatures of loss and recovery of consciousness from propofol

Abstract: Significance Anesthesiologists reversibly manipulate the brain function of nearly 60,000 patients each day, but brain-state monitoring is not an accepted practice in anesthesia care because markers that reliably track changes in level of consciousness under general anesthesia have yet to be identified. We found specific behavioral and electrophysiological changes that mark the transition between consciousness and unconsciousness induced by propofol, one of the most commonly used anesthetic drugs. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

70
874
9
20

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 677 publications
(973 citation statements)
references
References 77 publications
70
874
9
20
Order By: Relevance
“…Previous studies in humans have observed significant increases in slow oscillation power during loss of consciousness (7,12) and have established that these oscillations correspond to ON and OFF states where neurons are periodically silenced (11). Notably, unlike propofol-induced α waves, these slow oscillations are spatially incoherent (7,11), implying a state of "fragmentation" of cortical activity (11).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous studies in humans have observed significant increases in slow oscillation power during loss of consciousness (7,12) and have established that these oscillations correspond to ON and OFF states where neurons are periodically silenced (11). Notably, unlike propofol-induced α waves, these slow oscillations are spatially incoherent (7,11), implying a state of "fragmentation" of cortical activity (11).…”
Section: Discussionmentioning
confidence: 92%
“…In humans, a well-defined pattern of oscillations has been observed during transition into propofol-induced unconsciousness. This pattern includes β oscillations that smoothly transition into α oscillations at the time of loss of consciousness (7,8). EEG source localization analyses in humans suggest that these β and α oscillations are generated approximately within dorsal medial prefrontal and anterior cingulate cortices (16).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Shifts in these phase-amplitude coupling patterns may have significant implications for anesthetic depth but do not necessarily influence the algorithm that generates BIS values. A further salient example is that a transition to a pre-burst suppression electroencephalographic pattern (e.g., from a delta spindle pattern) can represent an increase in anesthetic depth.…”
Section: Bispectral Index Is a Limited Index Of Brain Functionmentioning
confidence: 99%
“…13 Des décalages de ces aspects de couplage phase-amplitude peuvent avoir des implications significatives pour la profondeur de l'anesthésie, mais sans nécessairement influencer l'algorithme qui génère les valeurs BIS. Un autre exemple marquant est qu'une transition vers un aspect EEG de suppression pré-salve (par exemple à partir d'un aspect de pointe-onde delta) peut représenter une augmentation de la profondeur de l'anesthésie.…”
Section: L'indice Bispectral Est Un Indice Limité De La Fonction Céréunclassified